Instrumentos de agregación de demanda como herramienta de gestión orientada a resultados: caso IAD emergencia Covid-19 (2020)
The purpose of this case study is to document the process The purpose of this case study is to document the process from the planning, structuring and implementation of the IAD COVID-19, which will allow to know the usefulness of this tool and the benefits associated with the public procurement process, building a new results-oriented spending approach, through the analysis of documents and interviews, accompanied by the most relevant actors among which the Business Sub-Directorate, citizens, suppliers, producers, and purchasing entities stand out. The above, taking into account the serious public calamity affecting our country due to the COVID-19 virus, which led the Government to declare a state of economic, social and ecological emergency in the National territory. Consequently, it allows the adoption of direct contracting mechanisms for the National Agency of Public Procurement Colombia Compra Eficiente (CCE), to design and implement the IAD COVID-19, which is aimed at the procurement of health care items, since it was identified that public entities were advancing abbreviated procurement processes to acquire the same goods or services, in limited quantities, uncertain quality and shortage prices, which generates an unnecessary administrative burden, raises prices and decreases the quality of goods, (CCE, 2020a).